How to cheat at managing windows server update services - Barber, Brian (Rockland, Mass. : Syngress, 2005)
Over 95% of computers around the world are running at least one Microsoft product. Microsoft Windows Software Update Service is designed to provide patches and updates to every one of these computers. The book will begin by describing the feature set of WSUS, and the benefits it provides to system administrators. Next, the reader will learn the steps that must be taken to configure their servers and workstations to make the compatible with WSUS. A special section then follows to help readers migrate from Microsofts earlier update service, Software Update Service (SUS) to WSUS. The next chapters will then address the particular needs and complexities of managing WSUS on an enterprise network. Although WSUS is designed to streamline the update process, this service can still be a challenge for administrators to use effectively. To address these issues, the next chapters deal specifically with common problems that occur and the reader is provides with invaluable troubleshooting information. One of the other primary objectives of WSUS is to improve the overall security of Windows networks by ensuring that all systems have the most recent security updates and patches. To help achieve this goal, the next sections cover securing WSUS itself, so that critical security patches are always applied and cannot be compromised by malicious hackers. * Only book available on Microsoft's brand new, Windows Server Update Services * Employs Syngress' proven "How to Cheat" methodology providing readers with everything they need and nothing they don't * WSUS works with every Microsoft product, meaning any system administrator running a Windows-based network is a potential customer for this book.
Ch. 1. Windows server update services essentials -- Ch. 2. Preparing for WSUS -- Ch. 3. Installing WSUS -- Ch. 4. Upgrading from SUS to WSUS -- Ch. 5. Deploying WSUS in the enterprise -- Ch. 6. Administering WSUS servers -- Ch. 7. Configuring and administering WSUS clients -- Ch. 8. Securing WSUS -- Ch. 9. Managing the WSUS environment -- Ch. 10. Using WSUS on a disconnected network -- Ch. 11. Troubleshooting WSUS.
Includes index.
Keywords: Microsoft Windows server; Client/server computing; Operating systems (Computers).; Microsoft Windows server; Electronic books